2017
DOI: 10.5812/iranjradiol.41928
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Positive Breast Cancer: Tumor-to-Liver SUV Ratio is the Best Parameter for Detection in F-18 FDG-PET/CT

Abstract: Background/Objectives: The purpose of this study was to assess the efficacy of pain control at a single center in a population of patients with osteoporotic fractures or vertebral metastasis after vertebroplasty (VP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In our study, the mean TLR and TSR had statistically significant relation with the molecular subtype of the breast tumor with P value = 0.018 and 0.061, it was found to be high among the HER2/Neu positive subtype tumors than among triple negative, luminal A and B subtype tumors. This finding agrees with Noda et al [22] who concluded a positive correlation between tumor to liver SUV max of the lesion with the molecular subtype (P = 0.0049) and agreed also with AbdElaal et al [23] who concluded that "the mean TLR values were much higher in Her2neu+, GIII and TN molecular subtype patients (P = 0.002, 0.0476, 0.005 and 0.018 respectively)…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the mean TLR and TSR had statistically significant relation with the molecular subtype of the breast tumor with P value = 0.018 and 0.061, it was found to be high among the HER2/Neu positive subtype tumors than among triple negative, luminal A and B subtype tumors. This finding agrees with Noda et al [22] who concluded a positive correlation between tumor to liver SUV max of the lesion with the molecular subtype (P = 0.0049) and agreed also with AbdElaal et al [23] who concluded that "the mean TLR values were much higher in Her2neu+, GIII and TN molecular subtype patients (P = 0.002, 0.0476, 0.005 and 0.018 respectively)…”
Section: Discussionsupporting
confidence: 90%
“…Tumor to normal (liver or mediastinum) uptake ratio proved highly reproducible [21]. Tumor to liver ratio (TLR) was superior to SUVmax in predicting colorectal recurrence, occult lymph node metastasis in lung carcinoma, malignant changes in plexiform neurofibromas in cases with neurofibromatosis type 1, and proved to be useful for identification of human epidermal growth factor receptor 2 overexpression (HER2+) subtype breast cancer [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%